Recovery of extracellular vesicles from human breast milk is influenced by sample collection and vesicle isolation procedures - Zonneveld, Marijke I. (Co-Action Publishing, 2014)
Extracellular vesicles (EV) in breast milk carry immune relevant proteins and could play an important role in the instruction of the neonatal immune system. To further analyze these EV and to elucidate their function it is important that native populations of EV can be recovered from (stored) breast milk samples in a reproducible fashion. However, the impact of isolation and storage procedures on recovery of breast milk EV has remained underexposed. Here, we aimed to define parameters important for EV recovery from fresh and stored breast milk. To compare various protocols across different donors, breast milk was spiked with a well-defined murine EV population. We found that centrifugation of EV down into density gradients largely improved density-based separation and isolation of EV, compared to floatation up into gradients after high-force pelleting of EV. Using cryo-electron microscopy, we identified different subpopulations of human breast milk EV and a not previously described population of lipid tubules. Additionally, the impact of cold storage on breast milk EV was investigated. We determined that storing unprocessed breast milk at −80°C or 4°C caused death of cells present in breast milk, leading to contamination of the breast milk EV population with storage-induced EV. Here, an alternative method is proposed to store breast milk samples for EV analysis at later time points. The proposed adaptations to the breast milk storage and EV isolation procedures can be applied for EV-based biomarker profiling of breast milk and functional analysis of the role of breast milk EV in the development of the neonatal immune system.